Asian traditional theatre and dance - Miettinen, Jukka O. (My University, 2018)
This vastly illustrated web-based material is an introduction to Asian theatre and dance traditions. It can be used as a virtual textbook for university students as well as a handbook for general readers. With its search-by-word facility it also serves as an encyclopaedia of names and terms related to the Asian performing arts. Twelve countries are included in the present, second edition of this on-line material (India, Sri Lanka, Myanmar, Thailand, Laos, Cambodia, Vietnam, Malaysia, Indonesia, China, Korea, and Japan). The focus is on the traditional forms of theatre and dance. The chapters that discuss the developments that have taken place in the 20th century in each country, however, include short descriptions of how the influx of Western theatrical aesthetics and conventions has influenced the traditional forms of theatrical arts of the country in question. The introductory chapter discusses those specific aspects of Asian traditions that differ from the Western ones, while the origins of theatrical traditions are also examined. Geographically, the material proceeds from west to east. Each chapter starts with a country profile and provides a map and essential information on population, ethnicities, languages, and religions. This profile is followed by a general introduction to the theatre and dance traditions of the particular country. Special attention is paid on the kind of information that early visual evidence, such as sculptures, gives about the early forms of Asian theatrical arts. The core chapters, dedicated to specific theatre and dance styles or traditions, describe what is known about their early developments as well as their present state. Altogether some 120 theatrical genres are introduced, each in its own chapter. Special attention is paid to the literary contents and acting techniques. Pop-up texts give further information about specific features, such as masks, costumes, and make-up conventions. Furthermore, synopses of important epics and dramas are provided in order to give the reader an overall view of the ideas the performances generate as well as the background to their cultural contexts. Additional articles give further in-depth information. The final article, "From East to West, from West to East" by Dr Anna Thuring focuses on the controversies in cultural exchanges between Asia and the Western world. Dozens of video clips and some 1200 photographs have been provided in order to visualise these colourful traditions with their intricate acting techniques and masks or make-up practices. Research and the compilation of information stretch back over three decades. I published my first book on Asian theatre in 1984 (Jumalia, sankareita, demoneja, Teak). Its section on Southeast Asia was further elaborated in my book published in 1992 (Classical Dance and Theatre in South-east Asia, Oxford University Press). The "forerunner" of this present material was the web-based material I compiled together with Mr. Veli Rosenberg in 1996 (Aasialaisen teatterin ja tanssin historia, Theatre Academy, Helsinki). My continual festival work in Finland and research abroad have also enabled me to study and document living Asian dance traditions further. My deepest thanks go to those numerous artists, colleagues, and photographers who have, through their various contributions, helped in creating this vast collection of material.
Keywords: Theater -- Asia -- History.; Dance -- Asia -- History.; Performing arts -- Asia -- History.; esittävät taiteet; teatteritaide; teatterihistoria; tanssi; tanssihistoria; Aasia; scenisk konst; teaterkonst; teaterhistoria; dans; danshistoria; Asien